ASSOCIATION BETWEEN FEMALE HORMONES (FSH, LH, AND ESTROGEN) AS WELL AS HYPERLIPIDEMIA AND OBESITY IN AL- NAJAF HOLY CITY - Worood Muslem Jubair (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
An excessively high level of lipids, or fat, in the blood is called hyperlipidemia. The levels of hormones in females were examined, along with their correlation with elevated body fat and impact on cardiovascular conditions. The information was gathered in Najaf City between November 1, 2023, and December 20, 2023. The results of this study showed that the concentrations for a hormone that promotes follicle development within samples had increased by 58%. LH increased in 50% of the samples that were analyzed. Better pubertal development has been associated with elevated FSH levels in the blood. Improved metabolism has been associated with an increase in blood FSH. Moreover, nonlinear correlations were found between adiposity measures and serum FSH levels.